IMPLEMENTASI PEMBELAJARAN CONCEPT MAPPING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS V SDN 1 CILOLOHAN KOTA TASIKMALAYA - Saridudin; Ulfah Nurfuadah (Program Studi Pendidikan Agama Islam, 2024)
Islamic Religious Education and Character Education at the Elementary Education level are taught using various methods. One of the learning methods used by teachers to achieve the desired goals of Islamic Religious Education is Concept Mapping. This learning method uses concept maps to help students understand the learning material. This study aims to analyze the implementation of Islamic Religious Education learning using the concept mapping method in class V SDN 1 Cilolohan. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through learning observations, interviews with teachers and students, and document analysis. The results of the study indicate that the implementation of Islamic Religious Education learning with concept mapping in class V SDN 1 Cilolohan Tasikmalaya City has gone well. Teachers can use the concept mapping method effectively to help students understand the learning material. Students also show high enthusiasm and participation in learning with this concept mapping method. Based on the results of the study, it is concluded that the concept mapping method contributes to helping teachers improve student learning outcomes in Islamic Religious Education learning in class V SDN 1 Cilolohan Tasikmalaya City. Therefore, this study recommends that the concept mapping method can be applied more widely at the Elementary School level